Association between serum uric acid to high-density lipoprotein ratio and all-cause in hypertensive patients: Mediating role of neutrophils - Chunyu Yan; Yabin Zhou; He Wang; Jiamei Fu; Qian Xu (PLoS ONE, 2025)
Background The aim of this study was mainly to investigate the association between Serum uric acid (SUA) to high-density lipoprotein cholesterol (HDL-C) ratio (UHR) and all-cause mortality in hypertensive patients,and to further investigate the mediating role of neutrophils. Methods Our cohort study included 4533 hypertensive patients drawn from the 2005–2018 National Health and Nutrition Examination Survey (NHANES) database and combined with the National Death Index (NDI) database to obtain mortality data for subjects. Kaplan-Meier survival curves, multifactorial Cox risk-proportional modeling, restricted cubic spline (RCS)-based smoothed curve fitting, threshold effects analysis, and subgroup analyses were performed to evaluate the associations between UHR and all-cause mortality, and, finally,causal mediating effects were performed to analyze the mediating role of neutrophils. Results Over a mean duration of 90.32 months, the follow-up all-cause mortality occurred in 1003 individuals, and the mean age of all subjects included was (61.69 ± 14.28) years, and the Kaplan-Meier survival curves demonstrated that high levels of UHR were notably connected to lower survival. In multivariate Cox regression analysis, high quartile UHR was positively connected to all-cause mortality (HR: 1.36, 95% CI: 1.03,1.80, P = 0.031), and smoothed curve fitting combined with threshold effect analysis showed a nonlinear relationship between UHR and all-cause mortality, with a curve inflection point of 0.14, i.e., when UHR < 0.14, an increase in UHR did not affect the increase in all-cause mortality (HR: 0.84, 95% CI: 0.06, 11.51, P = 0.8968), and when UHR > 0.14, the all-cause mortality increased with the increase in UHR. We further stratify by gender and find that the inflection point for male UHR is 0.13, the suggesting that the association between UHR and all-cause mortality increased with increasing UHR when UHR was < 0.13, HR (95% CI): 0.01 (0.00, 0.22), P < 0.01 and when UHR > 0.13, HR (95% CI): 0.41 (0.04, 1.36), P < 0.01. However there was a significant linear correlation for females (HR: 1.31 95% CI: 0.15, 11.55, P < 0.0001). Analysis of causal mediating effects elucidated that the proportion of neutrophils mediating the association between UHR and all-cause mortality was 18.63%. Conclusion There was a significant positive correlation between elevated UHR and all-cause mortality in hypertensive patients, and this association may be mediated with neutrophils.